Ultra-wideband bandpass filter with notch band based on quadratic Koch Island structure - Manju Bhaskar; Thomaskutty Mathew (IAES Indonesian Section, 2021)
An ultra-wideband bandpass filter with a notch band centered at 7.2 GHz is proposed to remove the interference caused by satellite communication signal coexciting within the ultra wide band. The filter comprises of two seperated quadratic koch island structures connected to the main transmission line to generate the notch band at the desired frequency. The designed ultra wide bandpass filter passes frequencies from 3.09 GHz to 10.61 GHz with a notch band from 7.12 to 7.46 GHz centered at 7.2 GHz and with a rejection level of 21.3 dB.The resonant frequency and bandwidth of the notch can be varied by the variation in the physical parameter of the filter. The proposed filter is fabricated, tested and compared with simulated results.